New training process planning methods for elite track and field athletes - Zelichenok, V. B.; Cherkashin, V. P.; Mironenko, I. N.; Mirzoev, O. M. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze the individualized training process design specifics for the modern elite track and field sports. The study data and analyses were used to produce recommendations on the training process design for the elite track and field sports with the relevant macro-, meso- and micro-cycles, and with the educational and training toolkits for every cycle. The recommendations are intended to help consolidate efforts of the developers and methodologists to facilitate the individualized training systems design and management process at the sport excellence and elite training stages as required by the valid Federal Sport Training Standards (FSTS) regulating the modern track and field sports.